The Impact of Russian Nationalism on Ethnic Conflicts in Soviet and Post-Soviet States - Marsili, M. (Democratization and Autocratization: IPSA 75th Anniversary Conference, 2024)
The Russian revolution of 1917 marked the transition from the tsarist autocracy to the communist autocracy. A multinational entity like its predecessor state—the Russian Empire—the Soviet Union was a federal union of 15 national republics, where 69 nationalities lived in 45 nationally delimited territories, having each ethnic groups their own ethnic affiliation, many of which exist to this day as ethnic republics within the Russian Federation. Russian functioned de facto as an official language of interethnic communication, with ethnic Russians dominating decision-making bodies. In an attempt to severe cultural, ethnic, and religious ties, and, ultimately, to "defuse ethnic tensions", the Soviet regime deported several nationalities, and ethnic groups were either widely dispersed, or these minorities were concentrated in areas already designated as the national republic for a different group. This policy involved the eradication of entire populations and their incorporation in alien territories, and, eventually, resulted in the forcible migration of over a million individuals. Nation-building process in former USSR republics suffered from forced displacement and resettlement which still contributes to fuel the ethnic discourse. This work explores the Russian policy on nationalities and the consequences on ethnic conflicts Soviet and in post-Soviet states.